Glycyrrhetinic acid protects against Multidrug-resistant Acinetobacter baumannii-induced lung epithelial cells injury by regulating inflammation and oxidative stress - Piaoyi Guo; Liang Jin; Huifen Zhou; Yida Bao; Jiehong Yang; Jing Chen; Yu He; Daojun Yu; Haitong Wan (BMC, 2023)
Abstract Glycyrrhetinic acid (GA) is a bio-effective component of Licorice. The GA is a monomer and the ingredient is an Oleanane-type pentacyclic triterpenes that has been used as a remedy for years. Due to the abuse of antibiotics, people pay attention to the emergence of Multidrug-resistant Acinetobacter baumannii (MDR-AB). As a conditional pathogen, MDR-AB causes severe infection, endangering human lives. Our previous studies found GA played an important role in Yinhua Pinggan, a Chinese medicine. However, whether GA could protect lung epithelium from MDR-AB-induced cell injury was elusive. Herein, we investigated the effects of GA on MDR-AB-infected A549 cells. The results showed GA had slightly antibacterial activity to MDR-AB in the GA (high concentration) but no impact on drug resistance genes. Notwithstanding, GA could reverse MDR-AB-induced cell apoptosis, hampered adhesion and invasion of MDR-AB to cells, and inhibit pro-inflammatory cytokines expression of IL-1β, IL-6, and TNF. Besides, MDR-AB-induced reactive oxygen species, pro-oxidative protein malonaldehyde, and myeloperoxidase of cells were decreased by GA, while antioxidative proteins were recovered, showing antioxidative capacity of GA might play a critical role. The expressions of toll-like receptor (TLRs) - 1, 2, 4, 5, 6, and 9 were increased by MDR-AB infection, while GA reversed the tendency. Interestingly, GA inhibited MDR-AB induced myeloiddifferentiationfactor88 expression (MYD88), one downstream con-factors of TLRs, but no affection on Interferon regulatory Factor 3 (IRF3), the other one, indicating GA inhibited MDR-AB induced cell injury by impact TLR/MYD88 pathway to attenuate inflammation. Altogether, our results demonstrated that GA protects against MDR-AB-induced cell injury through its antioxidative and anti-inflammatory properties, which deserve further study in the future.